Smartphone accelerometer-measured physical activity and adiposity indicators among female university students - Ahlam Saleh Alhajri (Digital Health)
Objective Physical inactivity (PI) is a major contributing factor to obesity, which is an increasing public health concern. This study aimed to examine the relationship between objectively measured physical activity (PA) and body mass index (BMI) among female university students. Methods A total of 600 female university students (mean age = 20.93 ± 1.12 years) participated in the study. Anthropometric measurements included weight, height, BMI, waist circumference, fat mass, muscle mass, and body fat percentage. Physical activity was assessed using smartphone-based accelerometers to measure step counts and calories burned. Results BMI classifications showed that 8.33% of participants were morbidly obese, 25% overweight, and 19% obese. Significant differences were found between BMI, fat mass, and muscle mass with both step counts and calories expended. Approximately 39.33% of participants were categorized as physically active, while the remaining 60.67% were inactive. Inactive students had higher fat accumulation and significantly fewer daily steps ( p  ≤ 0.05) compared to active students. Conclusion The findings reveal a high prevalence of obesity and PI among Saudi female university students. Active students had significantly lower BMI, waist circumference, fat mass, and body fat percentage than their inactive counterparts. Obese students were less active, had fewer steps, lower muscle mass, and reduced specific muscle strength. These findings underscore the urgent need for preventive health policies targeting overweight and obese female students in Saudi Arabia.